2013
DOI: 10.2478/v10114-011-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Above-ground net primary productivity in young stands of beech and spruce

Abstract: One of the expected consequences of climate change and its inherent phenomena to forest ecosystems is the gradual modification of their tree species composition (i.e. expansion of resistant species instead of less resistant ones). Climate change accompanied with increasing temperatures and a lack of precipitations may present a threat especially to spruce stands in the European part of the temperate zone. European beech is one of the possible forest tree species which might replace the potentially endangered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…Hence, the biomass (carbon) increased more in the beech than in the spruce stand that might be related not only to the inter-specific contrasts in the growth rates but also to the differences in their stand and site properties. In fact, also our previous study (Pajtík et al 2013) conducted in young beech and spruce stands grown at the identical sites indicated larger net primary productivity of beech than spruce. The difference occurred mainly due to the higher amount of assimilates allocated intobeech stems.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hence, the biomass (carbon) increased more in the beech than in the spruce stand that might be related not only to the inter-specific contrasts in the growth rates but also to the differences in their stand and site properties. In fact, also our previous study (Pajtík et al 2013) conducted in young beech and spruce stands grown at the identical sites indicated larger net primary productivity of beech than spruce. The difference occurred mainly due to the higher amount of assimilates allocated intobeech stems.…”
Section: Discussionmentioning
confidence: 94%
“…At the same time, we found much higher mortality rate in spruce than in beech young stands that was explained not only by different light conditions under the canopy but also by contrasting ecological properties of these species. Although our previous study Pajtík et al 2013) showed the results on biomass allocation and net primary productivity in developing young beech and spruce stands, we did not estimate either the amount of carbon sequestrated in tree biomass or the carbon flux realised via aboveground litter fall from living trees and body of died trees.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Це зумовлено відносною збалансованістю речовинного обігу між фітоценозом і ґрунтом, чого немає в антропогенно трансформованих екосистемах, до яких періодично вносять органічні та мінеральні добрива, додатково зрошують або осушують, а також регулярно вилучають із них частину біомаси. NPP лісових біогеоценозів залежить, головним чином, від видового складу деревостанів та їх біометричних характеристик: віку едифікаторних ценопопуляцій, абсолютної повноти, запасу та приросту стовбурної деревини та біомаси загалом (Tretjak and Chernevij, 2011;Pajtík et al, 2013;Vasylyshyn et al, 2014). Вирішальне значення має площа деревостанів сучасного біогеоценотичного покриву.…”
Section: вступunclassified
“…in Chile show R 2 aj values between 0.80 and 0.95. In addition, Pajtík et al (2013) showfor the allometric equations for expressing above-ground biomass on the basis of the diameter -a R 2 of 0.990 in reference to Norway spruce stem and a R 2 of 0.989 for the European beech stem in Slovakia. In the present study, the equation parameters show a high signifi cance level for both species (p < 0.001) and the Residual Standard Error (RSE) ranges between 0.66 and 0.77.…”
Section: R/s Ratiomentioning
confidence: 99%